Pengembangan Perangkat Pembelajaran Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar dan Literasi Sains Siswa pada Konsep Pembelahan Sel - Frida Maryati Yusuf; Elya Nusantari; Aryati Abdul; Hasna Abdan (Proceedings of The ICECRS, 2019)
This study aims to produce a learning tools based guided inquiry, suitable for use to increase student learning outcomes and scientific literacy on the concepts of cell division. Learning devices are developed using a design put forward by Borg & Gall. Learning tools validation by three validator. Trials practicality and effectiveness performed on students of class XII IPA 2 in SMA 1 Suwawa. Data collected analyzed qualitatively and quantitatively. Data validity analysis based on conversion quantitative data to qualitative data with a Likert scale. Data analysis implementation of learning, and student activities done on the results of observations. Data obtained from the results of the pretest and posttes were analyzed using the normalized gain formula. The results of the study show that learning tools developed show very valid criteria with an average score of validators for lesson plans with a minimum of 44 and LKPD of 19. Practicality and effectiveness of learning devices through limited trials shows that the learning process has a minimum score of 79, the activities of students get a minimum score of 77, with minimum criteria good; and mastery of students' concepts based on N-gain calculation get a minimum scores of 79 with minimum criteria of height. This shows that learning devices are developed meet the requirements of validity, practicality, and effectiveness, so that proper to use in learning.